Applying soft matter techniques to solve challenges in cryopreservation - Bryant, Saffron J.; Elbourne, Aaron; Greaves, Tamar L.; Bryant, Gary (Frontiers in Soft Matter, 2023)
Cryopreservation allows the long-term storage of biological material, and has become integral for numerous applications including assisted reproductive technologies, stem cell therapies, blood banking, and species preservation. However, there are still hundreds of cell types that cannot be cryopreserved, and no organs at all. The biggest challenge facing cryopreservation is the ongoing reliance on predominantly just two cryoprotective agents (dimethylsulfoxide and glycerol) as well as physical limitations to heating and cooling rates. The field of soft matter can accelerate cryopreservation research by providing insights into the underlying mechanisms and interactions of cells, cryoprotectants, and solvents including the role of temperature. With techniques as far ranging as differential scanning calorimetry, atomic force microscopy, and neutron and X-ray scattering, it is possible to probe multiple length and time scales in order to identify and characterise important interactions. This in turn can lead to the development of new cryoprotectants, and new methods of heating/cooling which could overcome some of the current challenges of cryopreservation.